Construction and validation of an instrument to assess the risk of suicide in Emergency and Psychosocial Care services (Research, Society and Development, 2025)
This article aimed to build and validate a protocol to be inserted into software to assess suicide risk, being a methodological development study carried out in three stages. In the first stage, the content was validated, through 5 judges, who were experts who work in teaching and research in the area of mental health and suicidology. After validating the content (protocol), the second stage was carried out, which consisted of the construction of the software by IT professionals. In the third stage, the software was validated in terms of applicability and usability. The study invited 19 participants, 17 professionals who work in the health network (urgency/emergency and mental health) of a municipality located in the north of the Minas Gerais triangle and two experts in the Information Technology (IT) field, who evaluated the interface and usability criteria. To validate all stages, participants used the Likert scale. The instrument obtained 80% agreement from judges regarding content, appearance, and consistency for assessing the risk of suicide in Emergency and Psychosocial Care services.